An unusual ryanodine receptor 1 (RYR1) phenotype: Mild calf-predominant myopathy. (2nd April 2019) - Jokela, Manu; Tasca, Giorgio; Vihola, Anna; Mercuri, Eugenio; Jonson, Per-Harald; Lehtinen, Sara; Välipakka, Salla; Pane, Marika; Donati, Maria; Johari, Mridul; Savarese, Marco; Huovinen, Sanna; et al.
Abstract : Objective: To identify the genetic defect causing a distal calf myopathy with cores. Methods: Families with a genetically undetermined calf-predominant myopathy underwent detailed clinical evaluation, including EMG/nerve conduction studies, muscle biopsy, laboratory investigations, and muscle MRI. Next-generation sequencing and targeted Sanger sequencing were used to identify the causative genetic defect in each family. Results: A novel deletion-insertion mutation in ryanodine receptor 1 ( RYR1 ) was found in the proband of the index family and segregated with the disease in 6 affected relatives. Subsequently, we found 2 more families with a similar calf-predominant myopathy segregating with unique RYR1 -mutated alleles. All patients showed a very slowly progressive myopathy without episodes of malignant hyperthermia or rhabdomyolysis. Muscle biopsy showed cores or core-like changes in all families. Conclusions: Our findings expand the spectrum of RYR1 -related disorders to include a calf-predominant myopathy with core pathology and autosomal dominant inheritance. Two families had unique and previously unreported RYR1 mutations, while affected persons in the third family carried 2 previously known mutations in the same dominant allele.